The role of endovascular expertise in carotid artery stenting: results from the ALKK-CAS-Registry in 5,535 patients - Staubach, Stephan; Hochadel, Matthias (Clinical research in cardiology, 2012)
Purpose: Several scientific committees have proposed an accentuation of operator minimal requirements before accreditation for carotid artery stenting is granted. The current study aims to identify potential effects from increasing site experience on periprocedural safety and outcome of carotid artery stenting (CAS). Methods: Between 1996 and December 2009, 5,535 procedures have been entered into the prospective, controlled ALKK-CAS-Registry. The total cohort was divided in four subgroups according to the consecutive patient order at each participating center: patients 1-49 (n = 1,485), 50-99 (n = 1,118), 100-199 (n = 1,521) and ≥200 (n = 1,411). Results: The median age of all patients was 71 years; 52.8 % had a symptomatic carotid stenosis. A decline in the rates of in-hospital major stroke (2.1, 1.9, 1.6, 0.9, p for trend 0.014) and of ipsilateral strokes (3.1, 2.4, 2.5, 1.6 %, p for trend 0.019) was substantiated with increasing site experience. This significant trend was preserved in the combined rate of major stroke and death (4.0, 3.2, 3.4, 2.4 %, p for trend 0.034). Apart from CAS experience, improvements in CAS technique, a decreasing number of symptomatic patients and an increasing number of procedures under embolic protection (each p for trend <0.05) might have contributed to these results. Conclusions: The results show a gradual reduction of in-hospital stroke rates with increasing center experience. Extensive supervision of CAS learners and further promotion of proctorship programs seem to be essential.